Mediasi Perceraian dalam Perspektif PERMA No. 1 Tahun 2016 dan Maqāṣid al-Syarī‘ah al-Syāṭibī: Analisis Normatif-Komparatif - Achmad Alparisi Maulana; Musleh Harry (Kartika: Jurnal Studi Keislaman, 2025)
The increase in divorce cases in Religious Courts shows the urgency of dispute resolution mechanisms that are not only efficient but also substantive in maintaining family resilience. PERMA No. 1 of 2016 places mediation as a strategic instrument to encourage a more peaceful resolution, but its implementation is often hampered by administrative orientation and superficial dialogue processes, so that the goal of public interest has not been fully achieved. On the other hand, maqāṣid al-Syarī‘ah al-Syāṭibī offers a philosophical framework that emphasizes family protection, damage prevention, and relationship restoration through the values of ḥifẓ al-nasl and ḥifẓ al-‘irdh. Using normative legal research methods through legislative, conceptual, and comparative approaches, this study assesses the alignment of the objectives of mediation according to PERMA with the values of maqāṣid. The results of the analysis show that there is a meeting point in the orientation of maintaining family integrity, but there are epistemological differences between the procedural approach of PERMA and the philosophical depth of maqāṣid. Therefore, this study recommends the integration of maqāṣid values into technical mediation guidelines and mediator training so that mediation not only fulfills formal obligations but also produces more humane dispute resolutions oriented towards long-term benefits